The Role of Kallikrein10 (KLK10) Polymorphism in Prostate Cancer Susceptibility: KLK10 polymorphism in Prostate Cancer - Güleç Yılmaz, Seda; Yencilek, Faruk; Yıldırım, Asıf; Akdeniz, Fatma Tuba; Dalan, Altay Burak; Barut, Zerrin; İsbir, Turgay (Urology Journal, 2021)
Purpose: The present study aims to investigate the potential role of Kallikrein 10 (KLK10) genotype and allele frequencies in predisposition to prostate cancer. Materials and Methods: KLK10 (rs7259451) gene polymorphisms were determined by real-time polymerase chain reaction analysis in patients with prostate cancer (n=69) and controls (n=76). Results: KLK10 gene frequencies were significantly different in the case and control groups (P = .028). GG carriers were significantly higher in the control group (P = .034), whereas TT carriers were higher in the prostate cancer group (P = .033). Furthermore, The patients with GG genotype had the lowest PSA levels while TT carriers had the highest (P = .005). Conclusion: According to the results, we suggested that carrying variant T allele and also carrying homozygote TT genotype could be a potential risk, while ancestral homozygote GG genotype and G allele are risk reducing factors for prostate cancer.